Primary Sources of Polycyclic Aromatic Hydrocarbons to Streambed Sediment in Great Lakes Tributaries Using Multiple Lines of Evidence. (11th June 2020) - Baldwin, Austin K.; Corsi, Steven R.; Oliver, Samantha K.; Lenaker, Peter L.; Nott, Michelle A.; Mills, Marc A.; Norris, Gary A.; Paatero, Pentti
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are among the most widespread and potentially toxic contaminants in Great Lakes (USA/Canada) tributaries. The sources of PAHs are numerous and diverse, and identifying the primary source(s) can be difficult. The present study used multiple lines of evidence to determine the likely sources of PAHs to surficial streambed sediments at 71 locations across 26 Great Lakes Basin watersheds. Profile correlations, principal component analysis, positive matrix factorization source‐receptor modeling, and mass fractions analysis were used to identify potential PAH sources, and land‐use analysis was used to relate streambed sediment PAH concentrations to different land uses. Based on the common conclusion of these analyses, coal‐tar–sealed pavement was the most likely source of PAHs to the majority of the locations sampled. The potential PAH‐related toxicity of streambed sediments to aquatic organisms was assessed by comparison of concentrations with sediment quality guidelines. The sum concentration of 16 US Environmental Protection Agency priority pollutant PAHs was 7.4–196 000 µg/kg, and the median was 2600 µg/kg. The threshold effect concentration was exceeded at 62% of sampling locations, and the probable effect concentration or the equilibrium partitioning sediment benchmark was exceeded at 41% of sampling locations. These results have important implications for watershed managers tasked with protecting and remediating aquatic habitats in the Great Lakes Basin. Environ Toxicol Chem 2020;39:1392–1408. © 2020 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Abstract : Comparison of US Environmental Protection Agency 16 priority pollutant polycyclic aromatic hydrocarbon compound (ΣPAH16 ) concentrations in select sediments around the world. Bar = mean; whisker = maximum.